Good, clean fun. (Cubao, Quezon City : Magnavision Home Video, 2000)
Learn about: good hygiene--Brushing teeth--Washing hands--Bathing and washing hair.
VCD Orig.
Keywords: Songs; Rhymes; Clealiness -- Film